A 15-Item modification of the PSP rating scale to improve clinical meaningfulness and statistical performance - Tien Dam; Lili Yang; Colin Gillis; Yumeng Li; John O’Gorman; Barbara Kolb; Adam L. Boxer; Lawrence Golbe; Samantha Budd Haeberlein; On behalf of the AL-108-231, PROSPERA, and 4RTNI investigators (Nature Communications)
Abstract Progressive supranuclear palsy (PSP) is a rare neurodegenerative disorder characterized by physical, cognitive, and behavioral impairments. The PSP Rating Scale (PSPRS) is a widely used and validated, clinical scale to monitor disease progression. Here we show the modification of PSPRS to improve clinical meaningfulness and sensitivity. A conceptual framework was used to select meaningful items. Datasets were analyzed to improve the psychometric properties, understand factor structure, and develop a scoring algorithm. Fifteen items of the PSPRS were selected based on whether the items reflect concepts specific to the disease and those responsive to change over 12 months. Some items were rescored to reflect meaningful changes and to improve discrimination and reliability. The rescored 15-item PSPRS was more interpretable and sensitive to disease progression over 12 months. The approach to develop the 15-item PSPRS provides an example of how to modify an existing clinical outcome assessment for use as a primary endpoint in a clinical trial of a progressive neurological disorder.